Incidence And Associated Factors Of Soil-Transmitted Helminth (STH) Infection Among Primary School Children - Irma Irma; Swaidatul Masluhiya AF (Universitas Tribhuwana Tunggadewi, 2026)
Soil Transmitted Helminths (STH) infection is a nematode worm infection that is transmitted through soil. STH infections often occur in elementary school children which can increase the risk of health problems such as diarrhea, reduced intelligence levels and malnutrition in children. This study aims to determine the incidence and factors correlated with the incidence of STH infection in children at SD Negeri 1 Lagundi, Kambowa District, North Buton Regency. This type of research is quantitative using a cross-sectional approach. The sample in this study was 85 respondents using a stratified random sampling technique. The research instrument used a questionnaire and laboratory tests. The analysis used is univariate and bivariate analysis using the SPSS Chi Square test with a confidence level of 95%. The results showed a relationship between cutting nails (p-value = 0.000), washing hands (p-value = 0.001), snacking carelessly (p-value = 0.481), taking worm medicine (p-value = 1.000) and history of worms (p-value = 0.049) with the incidence of STH in elementary school children. The conclusion of this research is that there is relationship between the habit of cutting nails, the habit of washing hands, and a history of worms with STH infection and there is no relationship between the habit of indiscriminate snacking and the habit of taking worm medicine and STH infection in elementary school children at SDN 1 Lagundi. It is necessary to provide education about clean and healthy living behavior to elementary school children by health workers and as well as a program to provide medication to prevent mass worm infections.